In Memoriam Ian Drummond Campbell 1910-2001 - Aikman, Colin (Victoria University of Wellington Law Review, 2001)
The funeral of Professor I D Campbell was held at Old Saint Pauls on Thursday 12 July 2001. Dr Colin Aikman, former Professor of Law, Victoria University of Wellington, delivered the following eulogy.